2017
DOI: 10.1371/journal.ppat.1006227
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium disrupts Sirt1/AMPK checkpoint control of mTOR to impair autophagy

Abstract: During intracellular infections, autophagy significantly contributes to the elimination of pathogens, regulation of pro-inflammatory signaling, secretion of immune mediators and in coordinating the adaptive immune system. Intracellular pathogens such as S. Typhimurium have evolved mechanisms to circumvent autophagy. However, the regulatory mechanisms targeted by S. Typhimurium to modulate autophagy have not been fully resolved. Here we report that cytosolic energy loss during S. Typhimurium infection triggers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 48 publications
(67 reference statements)
7
117
0
1
Order By: Relevance
“…Upon stimulation, AKT, a regulator of glucose homeostatis, phosphorylates mTOR thereby increasing muscle protein synthesis and muscle hypertrophy, as a result of which increase in muscle mass is expected. Further, Phosphorylated AKT is said to induce lysosomal degradation of SIRT1 by translocating it to the cytosolic region from the nucleus, by which antioxidant property of the cell is enhanced (Raja et al 2017). Previous reports states that, AKT, in addition to mTOR, phosphorylates wide range of proteins that includes FOXO.…”
Section: Resultsmentioning
confidence: 99%
“…Upon stimulation, AKT, a regulator of glucose homeostatis, phosphorylates mTOR thereby increasing muscle protein synthesis and muscle hypertrophy, as a result of which increase in muscle mass is expected. Further, Phosphorylated AKT is said to induce lysosomal degradation of SIRT1 by translocating it to the cytosolic region from the nucleus, by which antioxidant property of the cell is enhanced (Raja et al 2017). Previous reports states that, AKT, in addition to mTOR, phosphorylates wide range of proteins that includes FOXO.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, bacteria are subject to a variation of autophagy known as xenophagy, an evolutionarily conserved mechanism, which controls Salmonella replication (Birmingham et al , ; Jia et al , ; Benjamin et al , ; Conway et al , ). The autophagic response to Salmonella is transient and occurs early during infection (Tattoli et al , ; Ganesan et al , ). We found that expression of SipA during this early phase was required for optimal intracellular proliferation and, furthermore, that the requirement for SipA was dependent on autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…ULK1 phosphorylation and activation lead to autophagy induction (Alers et al, ; Russell et al, ; Wong et al, ). Ganesan et al () reported that S . Typhimurium SL1344 strain invades mouse bone marrow‐derived macrophages, the rupture of cell membranes and subsequent decrease of intracellular ATP levels lead to transient AMPK activation that occurs at 1 hr post infection.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that Salmonella can subvert autophagy by degrading AMPK activation and subsequently mTOR activation to evade host cell defences against the invading intracellular pathogens. But the question whether AMPK degradation leads to decreased ULK1 S555 and increased ULK1 S757 phosphorylation was not studied (Ganesan et al, ). Our present study demonstrated that S .…”
Section: Discussionmentioning
confidence: 99%